Organisasi produksi dan intervnsi koperasi persusuan di Jawa Barat - Thamrin, Juni (Project working paper series / West Java Rural Nonfarm Sector Research Project ;, 1992)
Organizational structure of milk industry and intervention of milk cooperatives in dairying business; case study in Kecamatan Pengalengan, Kabupaten Bandung and Kecamatan Cikajang, Kabupaten Garut, Jawa Barat Province.